Ethics Requirement Score: new tool for evaluating ethics in publications - Santos,Lígia Gabrielle dos (2014)
Objective To analyze ethical standards considered by health-related scientific journals, and to prepare the Ethics Requirement Score, a bibliometric index to be applied to scientific healthcare journals in order to evaluate criteria for ethics in scientific publication.Methods Journals related to healthcare selected by the Journal of Citation Reports™ 2010 database were considered as experimental units. Parameters related to publication ethics were analyzed for each journal. These parameters were acquired by analyzing the author’s guidelines or instructions in each journal website. The parameters considered were approval by an Internal Review Board, Declaration of Helsinki or Resolution 196/96, recommendations on plagiarism, need for application of Informed Consent Forms with the volunteers, declaration of confidentiality of patients, record in the database for clinical trials (if applicable), conflict of interest disclosure, and funding sources statement. Each item was analyzed considering their presence or absence.Result The foreign journals had a significantly higher Impact Factor than the Brazilian journals, however, no significant results were observed in relation to the Ethics Requirement Score. There was no correlation between the Ethics Requirement Score and the Impact Factor.Conclusion Although the Impact Factor of foreigner journals was considerably higher than that of the Brazilian publications, the results showed that the Impact Factor has no correlation with the proposed score. This allows us to state that the ethical requirements for publication in biomedical journals are not related to the comprehensiveness or scope of the journal.